REVITALISASI PASAR RAKYAT DAN DAMPAKNYA TERHADAP KEPUASAN DAN PENDAPATAN PEDAGANG - SUDJILAH - (Jurnal Akademika, 2020)
The transition from centralized to decentralization, every region implement autonomy including the management of people's markets. Based on Regulation of the Minister of Trade No. 56 / M-DAG / PER / 9/2014 the term "traditional market" is become as "People Market". Research focus: How the Implications of the People's Market Revitalization Policy to Increase Satisfaction and Income. Research Objectives: Knowing and Describing How the Implications of People's Market Revitalization Policies to Increase Satisfaction and Income of People's Market Traders. This research is a qualitative descriptive. Sources of the data, primary and secondary with observation techniques, interviews, library research and documentation. Population: Mojokerto Regency Industry and Trade Office, market traders, user communities. Random sample with Purposive sampling and Clustering Random Sampling techniques, the number of traders 50 people taken randomly at 6 market locations, 200 taken randomly at 6 community market locations. Data analysis was carried out in three stages, namely: reduction, presentation, and drawing conclusions. Results: Implications of the People's Market Revitalization Policy can Increase the Satisfaction and Income of People's Market Traders. Keywords:  revitalisation ,  satisfaction, income.